Factors Associated with Recent Use of Nicotine Replacement Therapy Among Multiethnic Smokers Residing in Public Housing. (10th November 2017) - Geller, Alan C.; Borrelli, Belinda; Davine, Jessica A.; Burtner, Joanna; Heeren, Timothy C.; Rees, Vaughan W.; Adegoke, Abdulkabir; Brooks, Daniel R.
Abstract : Introduction: Understanding factors associated with increased use of nicotine replacement therapy (NRT) is critical to implementing cessation interventions for low-income individuals yet the factors associated with NRT use among low-income smokers are poorly understood. Aims: Assess factors associated with NRT use among low-income public housing residents. Methods: ' Kick it for Good' was a randomised smoking cessation intervention study conducted among residents of public housing sites in Boston, MA. Secondary, cross-sectional analyses were conducted on smokers from a community-based intervention cessation intervention who reported making a quit attempt and use of NRT in the past 12 months ( n = 234). Results: Among smokers who made a quit attempt in the past year, 29% reported using NRT. Black (prevalence ratio, PR = 0.52, 95% CI: 0.38–0.71) and Hispanic (PR = 0.52, 95% CI: 0.31–0.88) participants were less likely to report use of NRT compared with Whites. The prevalence of recent NRT use was greatest among those both asking for and receiving provider advice (PR = 1.90, 95% CI: 0.96–3.78). Conclusions: Minority race and ethnicity and low provider engagement on NRT use were associated with lower NRT use. Providing barrier-free access to NRT and facilitating provider engagement with smokers regarding NRT use can increase NRT use among low-income populations.